2021
DOI: 10.1016/s2352-4642(21)00050-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors linked to severe outcomes in multisystem inflammatory syndrome in children (MIS-C) in the USA: a retrospective surveillance study

Abstract: Background Multisystem inflammatory syndrome in children (MIS-C) is a newly identified and serious health condition associated with SARS-CoV-2 infection. Clinical manifestations vary widely among patients with MIS-C, and the aim of this study was to investigate factors associated with severe outcomes. Methods In this retrospective surveillance study, patients who met the US Centers for Disease Control and Prevention (CDC) case definition for MIS-C (younger than 21 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
333
8
25

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(415 citation statements)
references
References 16 publications
49
333
8
25
Order By: Relevance
“…Of these, 2055 duplicate studies were removed; 1663 studies were excluded after title and abstract screening, and 202 were excluded following full text screening based on the set inclusion criteria. Twenty-four studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ] were ultimately included in the meta-analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 2055 duplicate studies were removed; 1663 studies were excluded after title and abstract screening, and 202 were excluded following full text screening based on the set inclusion criteria. Twenty-four studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ] were ultimately included in the meta-analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies [ 14 , 15 , [20] , [21] , [22] , [23] , [24] , [28] , [29] , [30] , [31] , [32] , [33] , 35 , 37 ] compared MIS-C and COVID-19, and nine of these studies [ 14 , 15 , [22] , [23] , [24] , 30 , 31 , 33 , 37 ] compared MIS-C with severe COVID-19. Eight studies [ [16] , [17] , [18] , [25] , [26] , [27] , 34 , 35 ] compared severe MIS-C with non-severe MIS-C, and three studies [ 17 , 19 , 26 ] compared MIS-C with CAA and MIS-C without CAA. The quality scores of the included studies ranged from 6 to 9, with three studies of moderate quality and 21 studies of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, vaccination may be particularly valuable for some subgroups. Certain chronic conditions, including obesity, predispose children to more severe covid-19,11 and those with markers of inflammation and cardiac distress, such as high levels of C reactive protein, interleukin-6, and brain natriuretic peptide, are more likely to develop serious sequelae such as multisystem inflammatory syndrome 12. Studies to identify whether laboratory markers before infection can predict risk of multisystem inflammatory syndrome should be a research priority, to help target vaccination to vulnerable children.…”
Section: Protectionmentioning
confidence: 99%
“…Among these is heart involvement [16]. Several findings seem to indicate that, in the first phases of severe COVID-19, signs and symptoms of heart lesions can occur and be useful to select children at risk for complications [13,17,18]. A great number of previously healthy children with MIS-C present with cardiovascular alterations [19][20][21].…”
Section: Risk Factors Associated With Severe Outcome Among Pediatric Patients With Covid-19mentioning
confidence: 99%
“…A great number of previously healthy children with MIS-C present with cardiovascular alterations [19][20][21]. Some of them already have signs and symptoms of heart dysfunction in the first phases of disease, and it has been reported that they increase the need for PICU admission, development of potential long-term problems, and risk of death [13,17,18]. Reduced left ventricular systolic function with an ejection fraction < 60%; diastolic dysfunction; and arrhythmias, including ST segment changes, QTc prolongation, and premature atrial or ventricular beat, were the earliest manifestations.…”
Section: Risk Factors Associated With Severe Outcome Among Pediatric Patients With Covid-19mentioning
confidence: 99%